Efeitos do treinamento resistido sobre a variabilidade da frequência cardíaca e a concentração sérica dos hormônios leptina, grelina e insulina em mulheres submetidas à gastroplastia - Araújo, Marlon Lemos de (2016)
The gastroplasty is considered the most effective intervention for weight reduction, but various changes are associated with surgery. The significant increase in the number of gastroplasty makes us study these changes and new interventions to optimize their beneficial effects and avoid some morbidities resulting in the postoperative period. The aim of the study was to evaluate the effects of resistance training on heart rate variability and the serum concentration of leptin, ghrelin and insulin in women undergoing gastroplasty. The sample consisted of 21 women. The patients were submitted to resistance training sessions, after medical release for four weeks. We evaluated anthropometric data, body composition, heart rate variability, and lipid profile and hormone levels in five periods. Data were expressed as mean and standard deviation. We used the Shapiro-Wilk test to determine if the sample was homogeneous. The comparison of data on body composition serum levels of the hormones studied was based on the implementation of the One-way ANOVA with Tukey post-test and Friedman test. We used the Pearson and Spearman correlation test to evaluate the correlation between hormones and indexes of body composition. Data were analyzed by BioEstat 5.0 software, considering statistically significant p ≤ 0.05. At the end of the twelve weeks of training the body mass Total preoperative significantly reduced from 106.20 kg to 84.63 kg. The body mass index of 41.18 kg / m2 to 32.78 kg / m2. Serum ghrelin levels in the same period was 293.50 pg / mL to 186.46 pg / ml. The leptin 34.42 ng / mL to 21.07 ng / mL. Insulin 21:33 U / mL to 11.22 U / ml. Resistance training together gastroplasty provided significant benefits in all variables. However there were no significant correlations between hormone levels with Total Body Mass, Body Mass Index and the Heart Rate Variability.